Monitoring of transplanted liver health by quantification of organ-specific genomic marker in circulating DNA from receptor. - Hada C Macher; Gonzalo Suárez-Artacho; Juan M Guerrero; Miguel A Gómez-Bravo; Sara Álvarez-Gómez; Carmen Bernal-Bellido; Inmaculada Dominguez-Pascual; Amalia Rubio (PLoS ONE)
Background Health assessment of the transplanted organ is very important due to the relationship of long-term survival of organ transplant recipients and health organ maintenance. Nowadays, the measurement of cell-free DNA from grafts in the circulation of transplant recipients has been considered a potential biomarker of organ rejection or transplant associated complications in an attempt to replace or reduce liver biopsy. However, methods developed to date are expensive and extremely time-consuming. Our approach was to measure the SRY gene, as a male organ biomarker, in a setting of sex-mismatched female recipients of male donor organs. Methods Cell-free DNA quantization of the SRY gene was performed by real-time quantitative PCR beforehand, at the moment of transplantation during reperfusion (day 0) and during the stay at the intensive care unit. Beta-globin cell-free DNA levels, a general cellular damage marker, were also quantified. Results Beta-globin mean values of patients, who accepted the graft without any complications during the first week after surgery, diminished from day 0 until patient stabilization. This decrease was not so evident in patients who suffered some kind of post-transplantation complications. All patients showed an increase in SRY levels at day 0, which decreased during hospitalization. Different complications that did not compromise donated organs showed increased beta-globin levels but no SRY gene levels. However, when a donated organ was damaged the patients exhibited high levels of both genes. Conclusion Determination of a SRY gene in a female recipient's serum is a clear and specific biomarker of donated organs and may give us important information about graft health in a short period of time by a non-expensive technique. This approach may permit clinicians to maintain a close follow up of the transplanted patient.